Muling Paglikha sa Mito ng Paglikha: Feministang Pagsasalaysay sa Kung Bakit Umuulan ni Rene O. Villanueva - Evasco, Eugene Y. (Philippine Humanities Review, 2015)
The paper centers on Rene Villanueva’s feminist retelling of “Tungkung Langit at Alunsina,” a Panay creation myth. The paper examines the context, types, and different methods of retelling in Philippine children’s literature. It also focuses on sexism in folklore and fairy tales which are the basis of modern children’s literature retelling. Through close reading, this paper shows how the art of retelling can transform sexist folklore to politically correct and gender fair text. Villanueva, the reteller, achieves this by representing the folklore’s passive female characater as a powerful creator of the universe. This modern female representation becomes the positive role model for the young readers.